PENGELOLAAN OBJEK WISATA PANTAI MUARO BINGUANG KABUPATEN PASAMAN BARAT - Purwita, Peni; Silfeni, Silfeni; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aim to know how to management of tourism Muaro Binguang Beachwhich consist of 4 indicator: ( a) planning, ( b) organizing, ( c) actuating, and ( d) controlling.This research is descriptive of qualitative. Question of this research is how management oftourism Muaro Binguang Beach. Data collection technique is done by using the methode ofinterviews, observation, and the documentation that involves the manager of the object of tourismas well as the community surounding tourist object and tourists. A qualitative data analisystechnique that includes three activity lines are data reduction, data presentation, and conclusion.Based on the result of research found some matters relating to the management of tourism MuaroBinguang Beach : 1. planning, 2. organizing, 3. actuating, and 4. Controlling in Muaro BinguangBeach. Planning related to the goal to be achieved in the long term as an integreted marinetourism area the provides comfort and security during the tour. For the sort term as a tourismthat increase viewed from four aspects are Amanites, Accesibilities, Ancillary, and Attaraction.Key word : Management, Tourism, Beach